Carbon markets from 2005 to 2010: minor malfunction or fundamental failure? Recommendations for institutional and agenda reform. Issue 2 (April 2011) - Gray, Matthew
From a societal and economic perspective, dangerous climate change is a considerable threat. With the advent of the 1997 Kyoto Protocol, the carbon markets have long been the dominant mechanism to tackle this threat. Through the EU Emissions Trading System (EU ETS) and the Clean Development Mechanism (CDM), this article critically reviews the carbon markets from 2005 to the present day. With stalled emissions trading systems in the USA, Japan and Australia, the carbon markets have lost considerable political footing outside Europe. Beyond the economic downturn of 2008 and underachievement at Copenhagen in 2009, this loss of political traction can be partially attributed to controversial events played-out within the EU ETS and the CDM. Despite controversies and the current political paralysis outside Europe, I argue that the carbon markets are still well placed to remain a dominant fixture amongst the potential policy options, and make a significant contribution in mitigating dangerous climate change. Institutional learning from the EU ETS and the CDM; an honest discussion with the ''real'' economy; carbon price disclosure to energy consumers; and a fully integrated approach to mitigating climate change will be critical to ensure the carbon markets become a dominant fixture outside of Europe. Policy recommendations are included in this regard.